Here, "f(y)=\\dfrac{4}{y-2}\\;and\\;g(x)=\\dfrac{5}{3x-1}.\\\\ \\\\"
"\\mathbf{To\\;find\\;: Domain \\;of\\;f \\circ g.}"
"\\mathbf{Now,\\;(f\\circ g)(z)=f(g(z))=f\\bigg(\\dfrac{5}{3z-1}\\bigg)=\\dfrac{4}{\\dfrac{5}{3z-1}-2} }"
"\\mathbf{=\\dfrac{4}{\\dfrac{5-2(3z-1)}{3z-1}}=\\dfrac{4(3z-1)}{5-6z+2}=\\dfrac{12z-4}{7-6z}}"
"\\mathbf{Clearly,\\; f\\circ g \\; is\\; defined\\;on\\;\\R\\; except\\;when\\; the\\; denominator\\;is\\;zero,i.e.,\\; when}"
"7-6z=0\\;\\implies z=\\dfrac{7}{6}"
"\\mathbf{So,\\;domain\\;of\\;f\\circ g=\\R-\\{{\\dfrac{7}{6}}\\}=(-\\infty,\\dfrac{7}{6})\\cup(\\dfrac{7}{6},-\\infty)}"
Graph of f :-
Graph of g :-
Graph of f o g :-
Comments
Leave a comment